Osteoporosis Among Tuberculosis Patients In Penang, Malaysia: Evaluation Of Treatment Outcomes, Knowlegde And Health Beliefs - Bhatti, Zohra (2021)
The present study aimed to assess the prevalence of osteopenia and osteoporosis, delayed sputum conversion rate and TB treatment outcomes among TB patients with weak bone health, the knowledge and health belief towards osteoporosis among study participants in Penang.